Multidisciplinary approach in the treatment of spin diseases - Chukhraev, N. V.; Zukow, W.; Unichenko, A. V.; Butskaya, L. V.; Gres, O. O. (Journal of Education, Health and Sport, 2019)
The article discusses the method of multidisciplinary treatment of patients with a diagnosis of M54.5 "Low back pain" based on the combined use of physiotherapy, kinesitherapy and correction of anxious depression. It was established that treatment of patients with lower back pain based on the proposed method reduces the level of subjective assessment of pain according to the VAS scale by 28 ± 3% reduces the clinical manifestations of pain and by 21 ± 4% the level of depression according to A. Beck’s psychometric table compared to the control group.